SIWA TATTWA PURANA [RITUAL-RITUAL KEHIDUPAN DAN KEMATIAN] - I Gde Agus Darma Putra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Shiva Tattwa Purana means ancient stories about the nature of Shiva. This story is begins with a description of Sang Hyang Jagatpati who is in Shiva Loka. Jagadpati is another name for Shiva. Shiva Tattwa Purana provides information and knowledge about Padma Bhuwana, Rituals of Life and Rituals of Death. Padma Bhuwana is a mystical-geographical map. The Ritual of Life according to Shiva Tattwa Purana begins with the union of Smara and Ratih in Cantik Gedong Mas. The ceremony while in the stomach is Pagedong-gedongan. Afterwards continue with the ceremony at twelve days, during a month, three months, six months, start walking and teething, matatah, getting married, then Apodgala. Rituals of Death can be done on people who have a corpse and does not have. This death ritual is carried out starting from the Atiwa-tiwa, Nyekah, Mukur, Ligya to Angluwer levels.